Đặc trưng văn hóa vùng miền qua một số tín hiệu thẩm mĩ thuộc trường nghĩa thực vật trong ca dao Nam Trung Bộ./Nguyễn Thị Vân Anh - Nguyễn, Thị Vân Anh
In Vietnamese, each region has its own culture so unique, rich and diverse. Folk songs clearly reflect the psychology, habits, living concept, and the culture of the nation. This is evidenced through an analysis of aesthetic signals of the plants in the Central South’s folk songs. The aesthetic signals in general and aesthetic signals of the plants in the Central South’s folk songs in particular bear in themselves the nation’s cultural values.